Aplasia of the Major and Minor Salivary Glands: Report of a Rare Case - Erofili Papadopoulou; Evangelia Piperi; Maria Georgaki; Emmanouil Vardas; Nikolaos G. Nikitakis (Stilus Optimus, 2022)
Background: Aplasia of the salivary glands, either partial or involving all the major and possibly the minor salivary glands, is a very rare cause of hyposalivation. The aim of this case report is to present a case of aplasia of the major and minor salivary glands and discuss the relevant literature. Methods: A 23-year-old woman, with a non-contributory medical and family history was referred due to rampant caries, that could not be attributed to any obvious aetiology. No sicca symptoms, previous parotid gland swelling or general symptoms were reported. Clinically, oral mucosa dryness and extended dental erosions and caries were observed, while the orifices of the excretory ducts of the parotid and submandibular salivary glands were not evident. Unstimulated and stimulated saliva flow rates were severely diminished, while a diagnostic biopsy of the lower lip revealed absence of minor salivary glands. Detailed hematologic and immunological investigations to exclude systemic disorders were also within normal limits. Ultrasound and magnetic resonance imaging revealed the absence of all major salivary glands, confirming the clinical diagnosis of congenital aplasia of the salivary glands. Results: Oral hygiene instructions and dietary advice were given while dental products with fluoride and saliva substitutes were administered and appropriate dental treatment was implemented. Regular dental follow-up was also advised. Conclusions: Timely diagnosis of aplasia of the salivary glands is important, considering the detrimental effects of the absence of saliva on oral health. Management consists of the use of saliva substitutes, nutritional adaptation, maintenance of oral health and regular dental follow-ups.